2005
DOI: 10.1212/01.wnl.0000159399.81861.d5
|View full text |Cite
|
Sign up to set email alerts
|

An open label study of the effects of rituximab in neuromyelitis optica

Abstract: Eight patients with worsening neuromyelitis optica were treated with rituximab to achieve B cell depletion. Treatment was well tolerated. Six of eight patients were relapse free and median attack rate declined from 2.6 attacks/patient/year to 0 attacks/patient/year (p = 0.0078). Seven of eight patients experienced substantial recovery of neurologic function over 1 year of average follow-up. The pretreatment median Expanded Disability Status Scale score was 7.5, and at follow-up examination was 5.5 (p = 0.013).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
343
0
18

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 595 publications
(376 citation statements)
references
References 8 publications
15
343
0
18
Order By: Relevance
“…Prednisone, azathioprine, and mycophenolate mofetil have all been effective in disease stabilization and relapse reduction in uncontrolled trials of NMO (41)(42)(43). The use of rituximab has been successful in a case series of patients with resistant disease (44). Notably, we have treated 1 patient (patient 5) with low-dose (500 mg) rituximab every 6 months, which has halted recurrence of myelitis.…”
Section: Discussionmentioning
confidence: 99%
“…Prednisone, azathioprine, and mycophenolate mofetil have all been effective in disease stabilization and relapse reduction in uncontrolled trials of NMO (41)(42)(43). The use of rituximab has been successful in a case series of patients with resistant disease (44). Notably, we have treated 1 patient (patient 5) with low-dose (500 mg) rituximab every 6 months, which has halted recurrence of myelitis.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of NMO from multiple sclerosis is also of great importance. The fact that several studies [19][20][21] have shown that patients with NMO present a better response to early therapy with immunosuppressive drugs than to therapy with immunomodulating agents emphasizes the importance of an early and accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the absence of attack-related inflammation could also release repair processes such as remyelination. Indeed, several studies investigating broad or selective immunosuppression reported an improvement of disability during the course of treatment [21,81,83,84,87,92,102,121,122].…”
Section: Discussionmentioning
confidence: 99%
“…It was the first specific immunosuppressant used for NMOSD. The pivotal open-label study from Cree et al [21] established B-cell depletion as a therapeutic principle for NMOSD; 6/8 patients were relapse-free after 1 year of treatment. Several clinical case series and retrospective analyses (including 10-55 patients each, treatment up to 8 years) have confirmed these findings and reported a reduction of ARR in 87-96 %, freedom from relapses in 44-72 %, and an improvement of disability in 80-100 % of patients [79,81,97,[99][100][101][102].…”
Section: Rituximab and Other B-cell-depleting Therapiesmentioning
confidence: 99%
See 1 more Smart Citation